Population biology of the ‘uçá'-crab, Ucides cordatus(Linnaeus, 1763) (Brachyura: Ucididae), in mangroves of the Joanes River, Bahia State, Brazil - Moraes, Elienai Elisia Bastos; Nunesmaia, Barbara Janaina Bezerra; Pinheiro, Marcelo Antonio Amaro (Sociedade Brasileira de Carcinologia, 2015)
ABSTRACTThis study evaluated the population structure, relative growth and morphological maturity size in Ucides cordatus in the Joanes River, Bahia State (Brazil). Crabs were sampled in a fragmented and human-altered mangrove ecosystem in a Brazilian Environmental Protected Area (EPA). A total of 431 crabs were sampled (265 males and 166 females) between September 2011 and August 2012. The following measurements were taken using precision callipers: carapace width (CW) and length (CL), the length of the propodus of the major cheliped (PL, males only), and the width of the 5th somite of the abdomen (AW, females only). Specimens were also weighed to a precision of 0.5 g on a scale to obtain the total wet weight (WW). The relative growth of this species was studied by using biometric relationships to estimate the morphological maturity size in both sexes (PLxCW in males and AWxCW in females). The overall sex ratio was 1.6:1, with a predominance of males (p & 0.05). The population structure of ‘uçá'-crabs was composed of two normal curves (juveniles and adults) in both sexes. A relative growth analysis using the CLxCW relationship revealed a negative allometric growth in adult males whereas adult females exhibited an isometric growth, with an inverse pattern occurring in juveniles. In males, the PLxCW relationship indicated a change in allometric growth at 39.4 mm CW (isometric growth in juveniles changing to positive allometry growth in adults). In females, the AWxCW relationship indicates that morphological maturity occurs at a delay (44.5 mm CW) and that growth changes between phases (positive allometry to isometry). Isometric growth was found using the WWxCW relationship, also regardless of sex. A literature review combined with results previously published about this species in northeast Brazilian region suggests that U. cordatus had a seasonal reproduction during six months (from December to May), with a fattening season in the following six months (June to November). Joanes River is an environmental protected area, but had a high anthropic pressure by closed condos and marinas. Despite the high anthropic pressure on this EPA, the population structure and reproduction of U. cordatus did not appear to be affected.
Keywords: Estuary; Growth; Mangrove land crab; Maturity; Reproduction